A Multi-objective optimization for batch chemical reaction Processes: The trade-off between economy and safety. (16th January 2023) - Wu, Yi; Ye, Haotian; Dong, Hong-guang
Highlights: Multi-objective optimization framework with multiple feeding modes for batch reactors. Dow's F&EI with runaway criteria of temperature limit/ divergence as safety consider. Response time analysis for the optimal schemes selected from the Pareto solutions. Abstract: he thermal safety is always a challenging topic in the case of batch reactors carrying exothermic reactions. To reduce the risk of thermal runaway from both perspectives of likelihood and severity, it is desirable and practicable to develop a multi-objective optimization framework which can achieve trade-off between economy and safety. Therefore, this work provided an optimization framework for batch chemical reactor design with inherent safer operating and equipment parameters through maximizing yield of the target product while minimizing degree of Dow's fire and explosion index along with thermal runaway constraints. Thermal runaway criteria, including temperature limit and divergence criterion, are employed as safety constraints. The response time is calculated with the optimal schemes selected from the Pareto solutions by a multi-attribute decision-making method (MADM). Finally, two examples for specific reaction systems with given kinetics are performed to demonstrate the feasibility and validity of the proposed method.